Parameritannin A-2 from Urceola huaitingii enhances doxorubicin-induced mitochondria-dependent apoptosis by inhibiting the PI3K/Akt, ERK1/2 and p38 pathways in gastric cancer cells. (25th January 2020) - Liang, Lu; Amin, Aftab; Cheung, Wing-Yan; Xu, Rui; Yu, Rujian; Tang, Jinshan; Yao, Xinsheng; Liang, Chun
Abstract: Parameritannin A-2 (PA-2) is a natural product extracted from the stems of the plant Urceola huaitingii . Our previous studies have shown that PA-2 exhibits significant synergistic anticancer effects with doxorubicin (DOX) in HGC27 gastric cancer cell lines. Here we report that our isobolographic analysis confirms the synergistic cytotoxic effects of PA-2 and DOX in HGC27 cells. Flow cytometry and immunoblotting indicate that PA-2 enhances DOX-mediated apoptosis. Importantly, PA-2 enhances the intracellular accumulation of DOX in HGC27 cells. The combination of DOX and PA-2 remarkably increases the release of cytochrome C and the activation of caspase-3 and caspase-9, compared with DOX treatment alone. Moreover, PA-2 attenuates the DOX-induced activation of Akt, ERK1/2 and p38 signaling pathways, providing a molecular mechanism for the synergistic effects of DOX and PA-2 in the induction of apoptosis. In conclusion, our studies demonstrate that PA-2 and DOX synergistically induce mitochondria-dependent apoptosis as PA-2 inhibits the PI3K/Akt, ERK1/2 and p38 pathways in HGC27 cells. These findings suggest that the combination treatment with PA-2 and DOX may represent a potent therapy for gastric cancer. Highlights: PA-2 exhibits significant synergistic anticancer effects with DOX in HGC27 cells. PA-2 enhances the intracellular accumulation of DOX in HGC27 cells. PA-2 enhances DOX-mediated apoptosis. PA-2 attenuates the DOX-induced activation of Akt, ERK1/2 and p38 signaling pathways.